2019
DOI: 10.30979/rev.abeno.v18i4.757
|View full text |Cite
|
Sign up to set email alerts
|

Traditional lecture versus PBL tutorials in Dental students’ knowledge acquisition

Abstract: Atualmente os educadores recomendam modelos mais dinâmicos focados no desenvolvimento do pensamento crítico, aprendizado ativo e solução de problemas. Este estudo quantitativo prospectivo teve como objetivo comparar o efeito de dois formatos de instrução - aulas tradicionais e aprendizagem baseada em problemas (ABP) - sobre o conhecimento de estudantes de odontologia do segundo ano em Radiologia Odontológica. Os estudantes foram alocados aleatoriamente em dois grupos: grupo controle n = 64 (tradicional) e grup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In contrast, Ratzmann et al (17) evaluated the effects of PBL in the orthodontic curriculum on the knowledge of students and found that the two groups of PBL and conventional learning were not significantly different in exams. In addition, Galvao et al (18) stated that PBL tutorials did not have a direct influence on knowledge acquisition of dental students in oral radiology. Regarding the endodontic curriculum of undergraduate students, Shao et al (19,20) showed that the conventional group was better than the PBL group with regard to basic theoretical knowledge scores; however, the teaching method did not affect the theoretical knowledge of postgraduate students.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ratzmann et al (17) evaluated the effects of PBL in the orthodontic curriculum on the knowledge of students and found that the two groups of PBL and conventional learning were not significantly different in exams. In addition, Galvao et al (18) stated that PBL tutorials did not have a direct influence on knowledge acquisition of dental students in oral radiology. Regarding the endodontic curriculum of undergraduate students, Shao et al (19,20) showed that the conventional group was better than the PBL group with regard to basic theoretical knowledge scores; however, the teaching method did not affect the theoretical knowledge of postgraduate students.…”
Section: Discussionmentioning
confidence: 99%